Dental Trauma. A Case Report - Alain Soto Ugalde; Berbardina Maya Hernández (Medisur)
Dental traumas in children are common; therefore the dentist should be trained to solve them. This paper presents the diagnosis, treatment and outcome of a child with a 12 mm overjet, mouth breathing habit and bilabial incompetence who suffered a severe trauma to tooth number 11, causing its mobility. A splint was applied to the affected tooth and subsequently, a root canal filling was performed, all with a satisfactory outcome. Although these traumas are common, the presentation of this case is important due to its use in the teaching context.